To solve the expression \(-\frac{12}{7} + \frac{3}{14}\), we need to find a common denominator for the fractions.
The denominators are 7 and 14. The least common denominator (LCD) is 14.
Now, convert \(-\frac{12}{7}\) to a fraction with the denominator of 14:
\[ -\frac{12}{7} = -\frac{12 \times 2}{7 \times 2} = -\frac{24}{14} \]
Now, we can rewrite the expression:
\[ -\frac{24}{14} + \frac{3}{14} \]
Combine the fractions:
\[ -\frac{24}{14} + \frac{3}{14} = \frac{-24 + 3}{14} = \frac{-21}{14} \]
Now, simplify \(\frac{-21}{14}\):
\[ \frac{-21}{14} = -\frac{21 \div 7}{14 \div 7} = -\frac{3}{2} \]
So, the result of \(-\frac{12}{7} + \frac{3}{14}\) is:
\[ -\frac{3}{2} \]